Alternative Splicing Regulation of Glycine-Rich Proteins via Target of Rapamycin-Reactive Oxygen Species Pathway in Arabidopsis Seedlings Upon Glucose Stress - Du, Chang; Bai, Hai-yan; Chen, Jing-jing; Wang, Jia-hui; Wang, Zhi-feng; Zhang, Zhong-hui (Frontiers in Plant Science, 2022)
Glucose can serve as both the source of energy and regulatory signaling molecule in plant. Due to the environmental and metabolic change, sugar levels could affect various developmental processes. High glucose environment is hardly conductive to the plant growth but cause development arrest. Increasing evidences indicate that alternative splicing (AS) plays a pivotal role in sugar signaling. However, the regulatory mechanism upon glucose stress remains unclear. The full-length transcriptomes were obtained from the samples of Arabidopsis seedlings with 3% glucose and mock treatment, using Oxford Nanopore sequencing technologies. Further analysis indicated that many genes involved in photosynthesis were significantly repressed and many genes involved in glycolysis, mitochondria function and the response to oxidative stress were activated. In total, 1220 significantly differential alternative splicing (DAS) events related to 619 genes were identified, among which 75.74% belong to intron retention. Notably, more than 20% of DAS events come from a large set of glycine-rich protein (GRP) family genes, such as GRP7, whose AS types mostly belong to intron retention. Besides the known productive GRP transcript isoforms, we identified a lot of splicing variants with diverse introns spliced in mRNA region coding the glycine-rich domain. The AS pattern of GRPs changed and particularly, the productive GRPs increased upon glucose stress. These ASs of GRP pre-mRNAs triggered by glucose stress could be abolished by AZD-8055, which is an ATP competitive inhibitor for the TARGET OF RAPAMYCIN (TOR) kinase, but could be mimicked by H2O2. Additionally, AS pattern change of ARGININE/SERINE-RICH SPLICING FACTOR 31(RS31) via TOR pathway, which is previously described in response to light and sucrose signaling, was also induced in a similar manner by both glucose stress and reactive oxygen species (ROS). Here we conclude that (i) glucose stress suppresses photosynthesis, activates the glycolysis-mitochondria energy relay and ROS scavenging system; (ii) glucose stress triggers transcriptome-wide AS pattern changes including a large set of splicing factors, such as GRPs and RS31; (iii) high sugars regulate AS pattern change of both GRPs and RS31 via TOR-ROS pathway. The results in this study will deepen our understanding in the alternative splicing regulation mechanism in sugar signaling.